Komunikasi Sebagai Moderasi Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan PT BPR Parasari Urati - Satya Dwiguna, I Made; Oka Ariwangsa, I Gusti Ngurah (Economic Reviews Journal, 2025)
This study aims to determine the influence of the work environment and organizational culture on employee performance, as well as to determine the moderating role of communication in the relationship between the work environment and organizational culture on employee performance. The sample in this study was 42 people. The data analysis technique used PLS 4. The results showed that the work environment has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, communication has a positive and significant effect in moderating the relationship between the work environment and employee performance, and communication has a positive and significant effect in moderating the relationship between social media promotion and employee performance. The researcher's recommendations include: PT BPR Parasari Urati should regularly provide employee training to improve their ability to complete tasks according to the specified target number, regularly maintain the air conditioning unit (AC) to ensure it consistently cools the room, foster strong relationships between employees, and consistently provide clear and detailed information to employees.